Censorship of the Siberian provincial newspapers: Linguistic and semantic correction - Zhilyakova, Nataliya V. (The European Proceedings of Social & Behavioural Sciences (EpSBS))
The article deals with typographic prints of the forbidden issue of Sibirskaya Gazeta (1881. No. 11), which are stored in the archives of the Main Directorate for Press Affairs (in the Russian State Historical Archive). The local censor M.A. Gilyarov, who replaced the permanent censor of Sibirskaya Gazeta, made remarks on prints. The proposed corrections caused a conflict between the censor and the editors of the newspaper, it reached the level of the General Directorate for Press Affairs. Petersburg requested typographic prints to clarify the circumstances of the conflict, which became, consequently, available to modern researchers. An analysis of typographic prints with censor's corrections showed that Gilyarov paid attention not only to the "ideological" component of presented texts. He struck out unnecessary words, apparently considering that the authors made a lexical mistake, corrected the forms of words, added the necessary, in his opinion, phrases. This suggests that the style of newspaper texts was also a matter of concern to provincial censors, despite the fact that they were not directly engaged in editing the texts. The conducted research leads to the conclusion that censorship of the provincial press was a much more complex phenomenon than a simple prohibition of "harmful" newspaper texts. The censors tried to moderate opposition statements of journalists and improve the style of the text in accordance with their ideas.